Obesity - Social Stigma - Depression - Teodoru, Veronica (New Trends in Psychology, 2022)
Obesity contributes to the increased incidence of diabetes, high blood pressure and heart disease. In addition, obesity can be a social stigma, as obese people are perceived as lazy and unwilling. Obesity is both a physical and a psychological disease, and a closer look will show that that psychological problems not only can foreshadow the development of obesity, but they are intrinsic to attempts to lose weight. The psychological factors that contribute to overeating include, on the one hand, a series of constraints that the person imposes on himself, and, on the other hand, the presence of disturbing emotional feelings. Discrimination against obese people extends beyond the medical practice. For example, at school, students face prejudice on the basis of extra pounds, which come from both colleagues and teachers, points out Dr. Puhl. Obesity discrimination occurs early on, studies suggest. Last but not least, there are social or economic factors that can be associated with childhood obesity. For example, a low level of education deprives the child of healthy eating habits.